Apatinib for the treatment of pulmonary epithelioid hemangioendothelioma: A case report and literature review. Issue 45 (November 2017) - Zheng, Zhipeng; Wang, Hanying; Jiang, Hanliang; Chen, Enguo; Zhang, Jun; Xie, Xinyou
Abstract: Rationale: Pulmonary epithelioid hemangioendothelioma (P-EHE) is a rare tumor, with no established standard treatment. Overexpression of vascular endothelial growth factor receptor 2 (VEGFR-2) has been reported in some P-EHE patients. Apatinib, a new small molecule tyrosine kinase inhibitor that specifically targets VEGFR-2, has therapeutic benefits in some advanced tumors. However, its efficacy in P-EHE cases has not been reported. Patient concerns: Herein, we presented a 44-year-old man with recurrent hemoptysis for approximately 9 years. Diagnoses: After hospitalization, relevant examinations were conducted. The disease was subsequently diagnosed as P-EHE. Interventions: The patient underwent pulmonary lobectomy, but subsequently developed multiple metastases. Within the tumor, CD31, CK, and Vimentin were found to be positive, while CD34 was negative. Apatinib was initially administered 250 mg daily doses and after 1 month was increased to 500 mg daily. Outcomes: He showed noticeable symptomatic improvements and positive imaging changes in the first month of treatment. However, the disease progressed in the following month, despite the increased apatinib dose. Lessons: Apatinib is possibly a new treatment for P-EHE. However, further clinical trials are necessary to confirm an effective dose and the efficacy and safety of apatinib in P-EHE treatment.